Comparative morphological and palynological study on poorly known Asperula serotina and its closest relative A. purpurea subsp. apiculata - (:unkn) unknown (My University, 2010)
Morphological and palynological features were examined in the closely related Turkish endemic taxa Asperula serotina and A. purpurea subsp. apiculata. Their morphological features showed very minor difference such as internodes length and the vein thickness of leaf, however, the seed and pollen characteristics clearly appear to have taxonomic value. The clavate-reticulate seed surface suture of A. serotina clearly differs from that lineate-sulcate of A. purpurea subsp. apiculata. Similarly, the pollen perforations and number of spines differ in each taxon. Moreover, the two taxa are geographically isolated from each other. Ecological features are also briefly discussed. The seed and pollen micromorphological properties could be used for intra/interspecific classification of Asperula which is taxonomically critical. © 2010 Academic Journals.
Keywords: Asperula; Morphology; Pollen; Seed; SEM; Taxonomy